PENGARUH ROLE MODEL ORANG TUA DAN EFIKASI DIRI TERHADAP MOTIVASI BELAJAR SISWA SMKN 1 SURABAYA - Putra, Franatan Krisna; Maula, Farij Ibadil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of Parental Role Models on Learning Motivation, the influence of Self-Efficacy on Learning Motivation, and the influence of Parental Role Models and Self-Efficacy simultaneously on Learning Motivation of students in the Office Management Expertise Program of SMK Negeri 1 Surabaya. This study uses a quantitative approach with a causal associative research type. The study population was 418 students of the Office Management Expertise Program of SMK Negeri 1 Surabaya consisting of students in grades 10, 11, and 12, with a sampling technique using proportionate random sampling so that a sample of 204 students was obtained. Data collection was carried out by distributing questionnaires for the variables of Parental Role Models, Self-Efficacy, and Learning Motivation. Data analysis techniques used validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis tests with the help of IBM SPSS Statistics 27. The results showed that Parental Role Models had a positive and significant effect on Learning Motivation with a significance value of 0.001 < 0.05. Furthermore, Self-Efficacy has a positive and significant effect on Learning Motivation with a significance value of 0.007 < 0.05. Simultaneously, Parental Role Models and Self-Efficacy have a positive and significant effect on Learning Motivation with a significance value of 0.001 < 0.05. The results of the coefficient of determination test show that both variables contribute 12.5% to learning motivation, while the remaining 87.5% is influenced by other factors outside the study. Thus, it can be concluded that parental role models as an environmental factor and self-efficacy as a personal factor play an important role in increasing the learning motivation of students at SMKN 1 Surabaya.